Coronary artery bypass grafting in a patient with active idiopathic cryoglobulinemia: revisiting the issue - Hafiz Abdul Moiz Fakih; Emmanuel Elueze; Rajiv Vij (Greater Baltimore Medical Center, 2016)
Background: Cryoglobulinemia is a cold-reactive autoimmune disease. It is of distinctive importance in cardiac surgery because of the use of hypothermic cardiopulmonary bypass (CPB). Cryoglobulins, which activate at variable levels of hypothermia, can cause precipitation during surgery leading to possibly severe leukocytoclastic or necrotizing vasculitis, clinically manifested as ischemic events, such as cutaneous ulcerations, glomerulonephritis, arthritis, or peripheral neuropathies among the most reported associated comorbidities. Management of CPB and systemic protection in this rare but unique scenario requires individualized planning. We report the case of a patient with active cryoglobulinemia who was preoperatively managed with plasmapheresis. He underwent hypothermic coronary bypass with no precipitation and flare during and after surgery. Case presentation: We describe the case of a 59-year-old Caucasian male with clinically significant idiopathic cryoglobulinemia and history of recurrent skin lesions and toe amputations secondary to cold exposure. He presented with 2-h duration of chest pain and new onset atrial fibrillation. After cardiac catheterization, a diagnosis of three-vessel coronary artery disease was established and coronary artery bypass grafting (CABG) was scheduled. Because of a high risk of flare-up during surgery, the patient was preemptively treated with two sessions of plasmapheresis before bypass. He then underwent hypothermic CABG. The pre- and perioperative course was unremarkable without any clinical evidence of precipitation. The patient was discharged on day 6 postoperatively without any complications. Conclusion: Preoperative plasmapheresis before hypothermic coronary bypass can prevent fatal cryoglobulinemia-related complications in patients with active disease.